Family History, Stress, Less Physical Activity, Obesity and Excessive Salty Food Consumption as Risk Factors of Hypertension - I Made Jaya Widyartha; I Wayan Gede Artawan Eka Putra; Luh Seri Ani (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: Hypertension was a significant public health problem. This study aims to determine risk factors of hypertension. Methods: The study used a case-control design, involving 77 cases and 77 controls aged 18-65 years old, who were selected consecutively. Cases and controls were matched on age and sex. Cases were defined as patients who were diagnosed with hypertension by clinician at the primary health center (PHC), and controls were patients at PHC who were not diagnosed as hypertension. Data were collected through interview regarding sosiodemographic status and risk factors of hipertension. Direct measurement was performed for weight, height and abdominal circumference. Multivariate analysis was conducted using logistic regression. Results: Cases and controls were comparable in term of sex, age and education level. Variables that associated with hypertension were family history (AOR=9.20; 95%CI: 3.47-24.41), moderate stress (AOR=13.01; 95%CI: 3.70-45.79), severe stress (AOR=16,75; 95%CI: 3,32-84,38), less physical activity (AOR=3.53 (95%CI: 1.38-9.01), obesity (AOR=5.72; 95%CI: 2.09-15.68) and excessive salty food consumption (AOR=3.08; 95%CI: 1.17-8.09). Eating fatty foods may also indirectly cause hypertension. Income, mild stress, smoking habits, being passive smokers, coffee consumption habits, frequency of fruits and vegetables consumption were not found to be risk factors. Conclusion: Family history, moderate and severe stress, less physical activity, obesity and excessive salty food consumption were risk factors of hypertension.